Model of quality costs and economic benefits of a business process of manufacturing companies. Issue 1 (1st January 2019) - Rosiawan, Muhammad; Laksono Singgih, Moses; Widodo, Erwin
Abstract: The objective of the study is to develop a mathematical model to measure the quality cost and economic benefits of the implementation of the quality improvement program within a business process of manufacturing companies. The economic benefits are obtained from saving quality costs resulting from achieving operational performance targets. The research methodology is used; firstly, the authors developed a conceptual model as a basis for a mathematical model. Secondly, they used a numerical experiment to illustrate the measurement of the effect of the change of the model parameters' values (e.g. number of performance indicators, and level target of performance target) toward the performance target achieved, cost savings obtained, and economic benefits. If the value of the model parameters increases, then the economic benefits will increase as well, and give a shorter return period of investment. And vice versa, if the value of the model parameters decreases, then the economic benefits will decrease as well and give a longer return period of investment. The model describes the dynamics of the quality costs and economic benefits periodically obtained from a quality improvement program.